Is economic growth a remedy for environmental degradation in oil-producing countries? New evidence from Africa - Abe, Magai; Zumba, Yunana Ishemu; Ladele, Ijeoma Stephanie (Energy Economics Letters, 2023)
The debate on the possibility of economic growth improving the quality of the environment has yet to reach a consensus. To contribute to this debate, we investigate the validity of the Environmental Kuznets Curve (EKC) hypothesis for oil-producing countries in Africa based on annual data from 1991 to 2019. We also examine the causal relationship between environmental quality and economic growth. The panel autoregressive distribution lag (PARDL) technique and the Granger non-causality test were employed. The findings show evidence of an inverted U-shaped relationship between economic growth and environmental quality in the long run, indicating the validity of the EKC hypothesis. It was also observed that energy prices exert strong, deteriorating effects on the environment in the short run. In the long run, renewable energy consumption and energy prices significantly improve the quality of the environment. The Granger causality test results demonstrate a unidirectional causality from environmental quality to economic growth. It was concluded that policies aimed at improving environmental quality in these countries could be beneficial in the short run. In the long run, these policies will prove beneficial only when economic growth is at a level where the quality of the environment is declining, since economic growth improves environmental quality.